2016
DOI: 10.21037/jgo.2016.03.11
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic hepatitis C and hepatitis C/HIV co-infection and the development of colorectal adenomas

Abstract: Background: Limited knowledge exists about the effects chronic hepatitis C virus (HCV) infection has in the development of colorectal adenomas (CRA). Data regarding the association between chronic HIV infection and the development of CRA is scarce as well. We aim to determine if there is an association between the development of CRA and chronic infection with HCV and HCV/HIV co-infection.Methods: From July 1, 2009 to March 31, 2011 a total of 2,051 patients that underwent colonoscopy were included in our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…Thus far, there are only two studies on this topic and the findings were inconsistent. Similar to our results, one study revealed that there was no statistical difference in the prevalence of colorectal adenoma between the HCV group and the control group (26.3%, n = 46/175 vs. 20.2%, n = 204/1008; adjusted OR, 1.02; 95% CI, 0.66-1.57; p = 0.93) [16]. However, unlike our findings, those of Rustagi et al showed that HCV infection was an independent risk factor for colorectal adenoma (37.8%, n = 88/233 vs. 30.3%, n = 141/466; adjusted OR, 1.47; 95% CI, 1.01-2.14), particularly advanced neoplasia (14.6%, n = 34/233 vs. 9.2%, n = 43/466; adjusted OR, 2.04; 95% CI, 1.20-3.49) [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus far, there are only two studies on this topic and the findings were inconsistent. Similar to our results, one study revealed that there was no statistical difference in the prevalence of colorectal adenoma between the HCV group and the control group (26.3%, n = 46/175 vs. 20.2%, n = 204/1008; adjusted OR, 1.02; 95% CI, 0.66-1.57; p = 0.93) [16]. However, unlike our findings, those of Rustagi et al showed that HCV infection was an independent risk factor for colorectal adenoma (37.8%, n = 88/233 vs. 30.3%, n = 141/466; adjusted OR, 1.47; 95% CI, 1.01-2.14), particularly advanced neoplasia (14.6%, n = 34/233 vs. 9.2%, n = 43/466; adjusted OR, 2.04; 95% CI, 1.20-3.49) [17].…”
Section: Discussionsupporting
confidence: 90%
“…However, little is known about the effects that HCV infection can have on the carcinogenesis of other common malignancies such as CRC. Although two previous studies have examined the association of HCV infection with the risk of colorectal adenoma, the results were inconsistent [16,17]. Drawing a reliable conclusion from the results of these studies is difficult.…”
Section: Introductionmentioning
confidence: 98%
“…An earlier US study found chronic HCV infection is associated 2-fold higher risk of colorectal adenoma in the distal colon ( 15 ). Hurtado-Cordovi and colleagues found an increased incidence of colorectal adenoma (26.3 vs. 20.2%) in patients with HCV than controls without HCV, but not significant ( 26 ). Moreover, a retrospective chart review study conducted by Prakash et al.…”
Section: Discussionmentioning
confidence: 96%
“…8 Besides HCC and ADM, only a few studies have assessed the risk of colorectal and pancreatic cancers among individuals with HCV, HBV, and/or HIV co-infection. 9 14 Furthermore, in most studies conducted to date, common underlying social and behavioral acquisition risks (e.g. injection drug use, problematic alcohol use) among infected individuals in the context of ‘disease syndemics’ have been inadequately addressed.…”
Section: Introductionmentioning
confidence: 99%